Penerapan Model Discovery Learning Untuk Meningkatkan Hasil Belajar Pada Tematik Terpadu Kelas IV SD (Studi Literatur) - Amna, Zikri Yanti; Muhammadi, Muhammadi (Universitas Negeri Padang, 2021)
Integrated thematic learning is integrated learning using themes that link several subjects so that learning provides meaningful experiences for students. In fact, learning outcomes in primary schools are not as expected. In connection with this problem, it is necessary to solve the problem to overcome it, one way to overcome this problem requires an appropriate learning model so that learning outcomes are optimal so that the results obtained by students can be satisfactory. One of the best models to solve this problem is the Discovery Lerning model. This study aims to provide benefits to readers in adding insight and knowledge about the application of the Discovery Learning model in the integrated thematic learning process. The type of research carried out is literature research. Based on the literature study research that researchers have done, it can be concluded that application of the Discovery learning model can provide an increase in student learning outcomes. It can be seen that learning using the Discovery Learning model, learning using the Discovery Learning model increases understanding for students so that learning outcomes in primary schools increase